2010
DOI: 10.1007/s10238-010-0124-3
|View full text |Cite|
|
Sign up to set email alerts
|

Hypocholesterolemia is associated negatively with hemolysate lipid peroxidation in sickle cell anemia patients

Abstract: The oxidative stress levels in plasma and hemolysate and cholesterol levels in plasma of sickle cell anemia patients, carriers and controls were evaluated. A total of 40 cases-17 patients, 13 carriers and 10 controls-were involved in the study. Plasma and hemolysate malondialdehyde (MDA) were detected via thiobarbituric acid reaction with a fluorimetric detector by high-performance liquid chromatography system. Plasma cholesterol was determined by enzymatic colorimetric method. Mean MDA levels of SCA patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 21 publications
1
10
0
Order By: Relevance
“…Oxidative stress can be another reason for hypocholesterolemia in SCA. In a recent study of our group a significant negative correlation was found between plasma cholesterol and hemolysate MDA levels of steady state SCA patients [6]. This data may indicate a decrease of either erythrocyte or plasma lipoprotein cholesterol perhaps due to a hypermetabolic state in response to oxidative stress.…”
supporting
confidence: 54%
“…Oxidative stress can be another reason for hypocholesterolemia in SCA. In a recent study of our group a significant negative correlation was found between plasma cholesterol and hemolysate MDA levels of steady state SCA patients [6]. This data may indicate a decrease of either erythrocyte or plasma lipoprotein cholesterol perhaps due to a hypermetabolic state in response to oxidative stress.…”
supporting
confidence: 54%
“…SCD is characterized by defect in plasma and erythrocyte lipids associated with chronic oxidative stress [6]. These two morbid processes disturb lipid homeostasis which in turn may lead to atherosclerosis in these patients [7, 8].…”
Section: Introductionmentioning
confidence: 99%
“…Besides the manifestations of chronic hemolysis, vaso-occlusion, endothelial injury and inflammation [1], SCA is also a disease of increased oxidative stress [2]. Previous studies have reported increased levels of malondialdehyde [2] and protein carbonyl [3] in the plasma of SCA patients.…”
Section: Tablementioning
confidence: 99%